Chemical quality analysis of solid organic fertilizer produced by BUMDEs Bangun Mandiri Bekiung Village, Langkat Regency from empty fruit bunches and liquid waste from palm oil mills - R B Moh Ibrahim Fatoni; Hafnes Wahyuni (Talenta Publisher Universitas Sumatera Utara, 2025)
Organic fertilizer is fertilizer made from decomposed plant, animal, and human waste, produced from various types of organic materials with different properties and characteristics. Bekiung Village is one of the villages that cultivates oil palm plants. However, the utilization of oil palm waste, such as fibers, empty fruit bunches, and liquid waste from oil palm mills, is still limited or has not been effectively utilized by the community, which can cause negative impacts on the environment if left to degrade, while on the other hand, this waste has a high nutrient content. The Community Service Activity based on the Community Empowerment Scheme in the form of making solid organic fertilizer from empty fruit bunches and liquid waste from palm oil mills was carried out at BUMDEs Bangun Mandiri, Bekiung Village, Langkat Regency, in August 2024. The preparation of tools and materials consisted of 100 kg of empty palm fruit bunches, 200 kg of dried palm oil mill effluent, and a bioactivator. Next, the grinding process was carried out using a Hummer mill machine. The results obtained were an organic fertilizer capacity of ±300kg with a fermentation time of 21-35 days with a nitrogen content of 0.21% in the low category, P2O5 of 0.12% in the medium category, K2O of 1.09% in the high category, C -Organic at 2.30% in the low category, Ca at 1.57 me/100g in the medium category, Mg at 0.49 me/100g in the high category, pH at 6.34 in the neutral category, and KTK and moisture content at 15.20 me/100g and 10.28%, respectively.